Peran Kepemimpinan Efektif dalam Meningkatkan Kualitas Organisasi Bem Fakultas Ekonomi : Penelitian - Alifah Salsa Khairan; Rona Dame Sianturi; Sapna Olivia Nababan; Rotua Sahat P Simanullang (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This study aims to analyze the role of effective leadership in building a solid work team and driving organizational development. Through a literature review, this research finds that effective leadership plays a key role in determining organizational success. Effective leaders not only act as decision-makers but also as motivators, directors, and inspirations for team members. Strong leadership can create a positive work environment, improve performance, and build a solid work team. This study also emphasizes the importance of leadership, where leaders serve as role models, mentors, and drivers who build trust, communication, and teamwork. The results of this study can serve as a reference for organizational and educational leaders to improve leadership quality and organizational development.